2011
DOI: 10.1155/2011/174306
|View full text |Cite
|
Sign up to set email alerts
|

Ion Transport by Pulmonary Epithelia

Abstract: The lung surface of air-breathing vertebrates is formed by a continuous epithelium that is covered by a fluid layer. In the airways, this epithelium is largely pseudostratified consisting of diverse cell types such as ciliated cells, goblet cells, and undifferentiated basal cells, whereas the alveolar epithelium consists of alveolar type I and alveolar type II cells. Regulation and maintenance of the volume and viscosity of the fluid layer covering the epithelium is one of the most important functions of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
139
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(144 citation statements)
references
References 171 publications
(284 reference statements)
0
139
0
5
Order By: Relevance
“…Previous literature suggested that ineffective clearance of fluid and malfunctions of pulmonary epithelial ion transport processes in fetal lung are major mechanisms for this pathology (12,13). Mechanical force of birth canal and Starling forces seem to have partially contribution to this process and fluid clearance is mainly mediated by the activation of transepithelial sodium reabsorption through the amiloride-sensitive epithelial sodium channels (ENaC) and sodium-potassium adenosine triphosphate ( Na + -K + -ATPase) activity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature suggested that ineffective clearance of fluid and malfunctions of pulmonary epithelial ion transport processes in fetal lung are major mechanisms for this pathology (12,13). Mechanical force of birth canal and Starling forces seem to have partially contribution to this process and fluid clearance is mainly mediated by the activation of transepithelial sodium reabsorption through the amiloride-sensitive epithelial sodium channels (ENaC) and sodium-potassium adenosine triphosphate ( Na + -K + -ATPase) activity.…”
Section: Discussionmentioning
confidence: 99%
“…The main function of K 1 channels, characterized by their high selectivity for K 1 over Na 1 (.100 to 1), is to control membrane potential, thereby maintaining the electrochemical gradient necessary for ion and fluid transport (Bardou et al, 2009). Chloride channels, including the cystic fibrosis transmembrane conductance regulator that plays a central role in alveolar ion transport (Lazrak et al, 2011), and other less well characterized Cl 2 channels, such as the ionotropicGABA A receptor (Jin et al, 2006), voltagegated Cl 2 channels, CLC5 and CLC2, and a basolaterally located Cl 2 channel (Berger et al, 2011), also contribute to lung liquid homeostasis (Hollenhorst et al, 2011). The current paradigm for liquid homeostasis in the adult mammalian lung is that passive apical uptake of Na 1 via ENaC and amiloride-insensitive CNG channels creates the major driving force for reabsorption of water through the alveolar epithelium (Matthay et al, 2005;Folkesson and Matthay, 2006;Berthiaume and Matthay, 2007;Hollenhorst et al, 2011;Wilkinson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the airways, a dynamic equilibrium between chloride secretion and sodium transport determines the volume and composition of the airway surface liquid (ASL). A precise volume of this liquid is necessary for proper ciliary beating and, hence, mucociliary clearance (38). Hypoactivity of ENaC, as in type 1 pseudohypoaldosteronism, will lead to an increased volume of the ASL (42), whereas hyperactivity of ENaC leads to ASL volume depletion and, consequently, both situations lead to impaired mucociliary clearance (50).…”
mentioning
confidence: 99%